Transivitas dalam Pidato Nadiem Makarim pada Peringatan Hari Guru Nasional 2021 - Angre, Audyna Gustia; Anwar, Miftahulkhairah (Nuances of Indonesian Language, 2023)
Transivity in Nadiem Makarim's Speech on the 2021 National Teacher's Day Commemoration This study aims to reveal the participants involved in the discourse (transivity) of Nadiem Makarim's speech on the 2021 National Teacher's Day commemoration. This research is a type of qualitative research. The data source for this research was obtained from Nadiem Makarim's speech text on the 2021 National Teacher's Day Commemoration, which was downloaded from the website www.youtube.com. The theory used is the Systemic Functional Linguistics (LSF) theory pioneered by Halliday. Data collection methods and techniques used are observation methods with note-taking techniques. The method of presenting the results of the data analysis used applies to the presentation of all forms of conversation in the research in the form of descriptions of words, phrases, groups of phrases, clauses, and texts. The results of the study show that the transivity in the speech text of Nadiem Makarim's Speech on the Commemoration of National Teacher's Day 2021 occurs through four processes. The four processes are material processes, mental processes, relational processes, and verbal processes; no behavioral or form processes are found. The four processes bind their respective participants and label these participants based on the processes that occur.